The Effectivity of E-Commerce in Increasing The Room Occupancy at Intercontinental Bali Resort, Jimbaran - Ni Kadek Eni Widyastuti; Ni Nyoman Sri Astuti; Dewa Made Suria Antara; Ni Gst Nym Suci Murni (Journal of Applied Sciences in Travel and Hospitality, 2020)
This study is based on the effectiveness of e-commerce implementation increasing room occupancy. It aims to find out how effective the implementation of e-commerce is and to find out the most effective variables in increasing the room occupancy at InterContinental Bali Resort. This research theoretically is expected to support other research by providing additional information regarding the development of e-commerce activities and practically is expected to be useful for hotel management to evaluate the effectiveness of e-commerce implementation. The data collection methods used in this research are documentation, interviews, and observations. The data analysis technique used is a quantitative analysis which is done through the calculation of the percentage of effectiveness using the effectiveness formula, and descriptive qualitative that is done to explain the information and data in the form of numbers collected during conducting research. Data processing is done using Microsoft Excel and the results of data analysis in the form of numbers, percentages, and graphs will be qualitative in the form of information to answer the problem formulation, make conclusions and suggestions for this research. The implementation of e-commerce which is examined in this research is through B2B and B2C strategies. Based on the analysis that has been done, the results show that the average effectiveness of e-commerce is reaching 100% or it is categorized as “Very Effective” and B2B strategy is more effective in contributing room occupancy because it can exceed the target to be achieved.